Comparative Study between Milligan Morgan Versus Ligasure Haemorrhoidectomy - Aftab Ahmad Baig, Muhammad Shahid Mehmood, Rizwan Khalid, Samar Ghufran, Salman Majeed Chaudhry, Hummaz Mehbub (Pakistan Journal of Medical & Health Sciences, 2022)
Purpose of Study: To compare the short term outcome of Ligasure haemorrhoidectomy with Milligan Morgan technique for third and fourth degree haemorrhoids. Design of Study: The present study was a single-blind randomized controlled trial. Duration and Location of Study: This trial was conducted at Akhtar Saeed Trust Teaching Hospital, Lahore. Duration of study is 6 months June 2021 to December 2021. Patients and Methods: A total of 80 subjects suffering from 3rd or 4th degree haemorrhoids were enrolled in the study and divided into two groups using lottery method. An informed written consent was taken from all the patients. Patients in group A (LS group) underwent Ligasure haemorrhoidectomy while patients in group B (MM group) underwent Milligan Morgan haemorrhoidectomy. Mean and standard deviation was calculated for numerical variables like age, operation time and postoperative pain on VAS score. Frequency and percentage was calculated categorical variables like gender, disease severity, bleeding, occurrence of urinary retention, anal stenosis and necrosis. SPSS version 22.0 was used for data analysis. Results of the Study: The patients had a mean age of 41.54±6.380 years within age range of 35-62 years. Number of male participants was high as 49 (61.3%) while compared with females who were 31 (38.7%) in total study sample of 80 subjects with a male to female ratio of 1.58:1. Number of patients with 3rd degree haemorrhoids was 53 (66.3%) whereas 27 (33.8%) patients had 4th degree haemorrhoids. LS was found to have significantly less operation time as 15.03±1.928 vs. 20.40±2.228 minutes; p-value=0.000. Postoperative pain was significantly less in LS group than MM group (4.20±0.883 vs. 5.23±0.891; p-value=0.000). Frequency of postoperative bleeding was also significantly less in LS group than MM group (5.0% vs. 25.0%; p-value=0.013). Occurrence of urinary retention was high in the LS group but the difference was not significant (p=0.247). Frequency of anal stenosis and necrosis was also less in LS group than MM group but the difference was not statistically significant with p-value=0.077 and 0.500, respectively. Conclusion: Ligasure haemorrhoidectomy was found superior to Milligan Morgan hemorrhoidectomy in managing patients with third and fourth degree haemorrhoids because it has considerably less operation time, postoperative pain and bleeding. Thus, Ligasure haemorrhoidectomy should be favored in the treatment of such cases in future surgical practice on the basis of benefits of Ligasure haemorrhoidectomy. Keywords: Hemorrhoids, Ligasure Haemorrhoidectomy, Milligan Morgan Hemorrhoidectomy